Non-Formal Education of the Indian Muslim Community in Medan at the Ghaudiyah Mosque and the Jamik Mosque - Pipi Darsina Siregar; Hasan Asari; Zaini Dahlan (MASI Mandiri Edukasi, 2026)
Mosques serve not only as places of worship but also as centers for community education and development. In multicultural urban areas such as Medan City, mosque-based non-formal education plays an important role in strengthening religious knowledge and social cohesion among minority Muslim communities. However, studies on the management of non-formal education within the Indian Muslim community remain limited, particularly regarding its planning, implementation, and evaluation. This study aims to describe these aspects in educational programs conducted at the Ghaudiyah Mosque and Jamik Mosque in Medan City. This research employed a qualitative approach using a multisite phenomenological design. Data were collected through observations, interviews, and documentation involving mosque administrators, foundation managers, community leaders, educators, and participants. Data were analyzed using the Miles, Huberman, and Saldaña interactive model, while data validity was ensured through source, method, and time triangulation. The findings indicate that educational programs are systematically planned through deliberation among foundation administrators, mosque management, community leaders, and teaching staff based on community needs. Program activities include regular Islamic studies, conversion guidance, Tahfiz House programs, women’s religious gatherings, and monthly recitations. Implementation is carried out through lectures, discussions, worship practices, mentoring, and Qur’anic memorization activities. Evaluation focuses on attendance, Qur’anic literacy and memorization, worship practices, and changes in participants’ religious behavior. The study concludes that mosque-based non-formal education contributes significantly to strengthening religious understanding, Islamic brotherhood, and the educational function of mosques. These findings enrich the literature on non-formal Islamic education and provide practical guidance for community-based educational development.